Bacteriophage‐mediated interference of the c‐di‐GMP signalling pathway in Pseudomonas aeruginosa. Issue 3 (12th December 2020) - De Smet, Jeroen; Wagemans, Jeroen; Hendrix, Hanne; Staes, Ines; Visnapuu, Annegrete; Horemans, Benjamin; Aertsen, Abram; Lavigne, Rob
Summary: C‐di‐GMP is a key signalling molecule which impacts bacterial motility and biofilm formation and is formed by the condensation of two GTP molecules by a diguanylate cyclase. We here describe the identification and characterization of a family of bacteriophage‐encoded peptides that directly impact c‐di‐GMP signalling in Pseudomonas aeruginosa . These phage proteins target Pseudomonas diguanylate cyclase YfiN by direct protein interaction (termed YIPs, YfiN Interacting Peptides). YIPs induce an increase of c‐di‐GMP production in the host cell, resulting in a decrease in motility and an increase in biofilm mass in P. aeruginosa . A dynamic analysis of the biofilm morphology indicates a denser biofilm structure after induction of the phage protein. This intracellular signalling interference strategy by a lytic phage constitutes an unexplored phage‐based mechanism of metabolic regulation and could potentially serve as inspiration for the development of molecules that interfere with biofilm formation in P. aeruginosa and other pathogens. Abstract : C‐di‐GMP is a key signaling molecule which impacts bacterial motility and biofilm formation and is formed by the condensation of two GTP molecules by a diguanylate cyclase. We here describe the identification and characterization of a family of bacteriophage‐encoded peptides that bind the Pseudomonas aeruginosa diguanylate cyclase YfiN and thereby impact c‐di‐GMP signaling. This intracellular signaling interference strategy by a lytic phage constitutes an unexplored phage‐based mechanism of metabolic regulation and could potentially serve as inspiration for the development of molecules that interfere with biofilm formation in P . aeruginosa and other pathogens.